Sexual Health of Polish Athletes with Disabilities - Plinta, Ryszard (Int J Environ Res Public Health, 2015)
The purpose of this study was to determine sexual functioning of Polish athletes with disabilities (including paralympians). The study encompassed 218 people with physical disabilities, aged between 18 and 45 (149 men and 69 women). The entire research population was divided into three groups: Polish paralympians (n = 45), athletes with disabilities (n = 126) and non-athletes with disabilities (n = 47). The quality of sexual life of Polish paralympians was measured by using the Polish version of Female Sexual Function Index and International Index of Erectile Function. Clinically significant erectile dysfunctions were most often diagnosed in non-athletes (83.33%) with 50% result of severe erectile dysfunctions, followed by athletes and paralympians with comparable results of 56.98% and 54.17% respectively (p = 0.00388). Statistically significant clinical sexual dysfunctions concerned lubrication, orgasm as well as pain domains, and prevailed among female non-athletes (68.42%, 68.42% and 57.89%). Practising sports at the highest level has a favourable effect on the sexuality of men and women with physical disabilities. Men with physical disabilities manifest more sexual disorders than women, an aspect which should be considered by health-care professionals working with people with disabilities.